2020
DOI: 10.1016/j.ijid.2020.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive enzyme-linked immunosorbent assay for the detection of MPT64 secretory antigen to evaluate Mycobacterium tuberculosis viability in sputum

Abstract: This study examined Mycobacterium tuberculosis (MTB)-secreted MPT64 as a surrogate of bacterial viability for the diagnosis of active pulmonary TB (PTB) and for follow-up treatment. Methods: In this proof-of-concept prospective study, 50 PTB patients in the Tokyo metropolitan region, between 2017 and 2018, were consecutively included and 30 healthy individuals were also included. Each PTB patient submitted sputum on days 0, 14 and 28 for diagnosis and follow-up, and each healthy individual submitted one sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The increased specificity and affinity of the antibody for its antigen is a desirable feature of reagents in immunological method-based POCTs. Recently, the use of an antibody tagged with alkaline phosphatase in conjunction with thionicotinamide-adenine dinucleotide (thio-NAD) for developing a sensitive immunoassay has been reported for the diagnosis of mycobacterium tuberculosis [52]. The multivalent maxibody platform, scFv-Fc-scFv, represents an excellent option for diagnosing gonorrheal infections.…”
Section: Discussionmentioning
confidence: 99%
“…The increased specificity and affinity of the antibody for its antigen is a desirable feature of reagents in immunological method-based POCTs. Recently, the use of an antibody tagged with alkaline phosphatase in conjunction with thionicotinamide-adenine dinucleotide (thio-NAD) for developing a sensitive immunoassay has been reported for the diagnosis of mycobacterium tuberculosis [52]. The multivalent maxibody platform, scFv-Fc-scFv, represents an excellent option for diagnosing gonorrheal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the similar performance of the culture-free ultrasensitive ELISA method and Xpert molecular tests, the culture-free ultrasensitive ELISA test is useful for monitoring the treatment response because this method detects only live bacilli [58] . When tuberculosis cases are under effective drug therapy, the culture-free ultrasensitive ELISA test may reveal negative results, whereas the molecular method might detect DNA from dead bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the effect of blood in specimens on the tests should be excluded in our test. The other is that the examination of drug effectiveness should be promoted more [58] . The studies according to a new design of drug monitoring for patients will be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…antigen during the entire research process because Mpt64 is only secreted from live bacilli, and studies have shown that Mpt64 can be used as a substitute for bacterial viability to diagnose patients with active tuberculosis [47,48]. We want to simulate the sustained release of proteins from living bacilli by stimulating stromal cells and immune cells to secrete cytokines and upregulate monocyte costimulatory molecules to affect CD4 + T cells.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%